Evaluation of Radiation Shielding Potential of Bismuth Boro-Tellurite Glasses - Kharb, Anil; Renu Sharma (RSYN Proceedings, 2025)
The increasing demand for effective and environment friendly radiation shielding materials has led to the exploration of bismuth boro-tellurite glasses as potential alternatives to conventional lead materials. This study investigated the radiation shielding potential of bismuth tellurite glasses having composition 15B₂O₃-xBi₂O₃-(85-x)TeO₂ where x =35, 40, 45, 50, 55 mol % & analyzed the mass attenuation coefficient (μ/ρ), effective atomic number (Zeff) & electron density (Ne) over a wide photon energy range of 0.015 MeV to 15 MeV using WinXcom software. The dependence of Zeff and Ne on photon energy and Bi₂O₃ concentration was evaluated to assess the material’s radiation shielding efficiency. The results indicated that the increasing Bi₂O₃ content enhances the photon attenuation due to the high atomic number and density of bismuth. It has been observed that the G5 glass sample exhibiting the maximum value of mass attenuation coefficient (μ/ρ), effective atomic number (Zeff) & electron density (Ne) and can be used as a promising material for radiation protection applications in nuclear medicine, space technology and high-energy physics.